Expression of Stromal Cell–Derived Factor-1 by Mesenchymal Stromal Cells Impacts Neutrophil Function During Sepsis. Issue 5 (May 2020) - Kwon, Min-Young; Ghanta, Sailaja; Ng, Julie; Tsoyi, Konstantin; Lederer, James A.; Bronson, Roderick T.; El-Chemaly, Souheil; Chung, Su Wol; Liu, Xiaoli; Perrella, Mark A.
Abstract : Objectives: Sepsis results in organ dysfunction caused by a dysregulated host response, in part related to the immune response of a severe infection. Mesenchymal stromal cells are known to modulate the immune response, and expression of stromal cell–derived factor-1 regulates mobilization of neutrophils from the bone marrow. We are investigating the importance of stromal cell-derived factor-1 in mesenchymal stromal cells and its role in promoting neutrophil function after the onset of cecal ligation and puncture–induced sepsis. Stromal cell–derived factor-1 expression was silenced in mesenchymal stromal cells, compared with the control scrambled construct mesenchymal stromal cells. Design: Animal study and cell culture. Setting: Laboratory investigation. Subjects: BALB/c mice. Interventions: Polymicrobial sepsis was induced by cecal ligation and puncture. shSCR mesenchymal stromal cells and shSDF-1 mesenchymal stromal cells were delivered by tail vein injections to septic mice. The mice were assessed for survival, bacterial clearance, and the inflammatory response during sepsis in each of the groups. Mesenchymal stromal cells were also assessed for their ability to promote bacterial phagocytosis by neutrophils. Measurements and Main Results: Injection of shSCR mesenchymal stromal cells after the onset of sepsis led to an increase in mouse survival (70%) at 7 days, whereas survival of mice receiving shSDF-1 mesenchymal stromal cells was significantly diminished (33%). The loss of survival benefit in mice receiving shSDF-1 mesenchymal stromal cells was associated with less efficient bacterial clearance compared with shSCR mesenchymal stromal cells. Although shSCR mesenchymal stromal cells, or their conditioned medium, were able to increase neutrophil phagocytosis of bacteria, this effect was significantly blunted with shSDF-1 mesenchymal stromal cells. Assessment of peritoneal inflammation revealed that neutrophils were significantly increased and more immature in septic mice receiving shSDF-1 mesenchymal stromal cells. This response was associated with hypocellularity and increased neutrophil death in the bone marrow of mice receiving shSDF-1 mesenchymal stromal cells. Conclusions: Expression of stromal cell-derived factor-1 in mesenchymal stromal cells enhances neutrophil function with increased phagocytosis, more efficient clearance of bacteria, and bone marrow protection from depletion of cellular reserves during sepsis. Abstract : Supplemental Digital Content is available in the text.